Tinjauan Estetika Bentuk Bangunan Dan Ragam Motif Keraton Ismahayana Landak Kalimantan Barat - Nia Agustin Ilzar Rahmahtillah; Dwi Candra Purnamasari (Lembaga Pengembangan Kinerja Dosen, 2023)
The study examines Keraton Ismahayana Landak as a national cultural heritage reflecting the glory of the Landak Kingdom in the past. Located in Desa Raja, near Ngabang city, the palace captivates with its beauty and artistic richness. A holistic approach was used for data collection through observation, interviews, and documentation to reveal the aesthetic value of the palace, including its physical aspects and decorative motifs. The unique architectural form and traditional Malay motifs portray the richness of nature, artist creativity, and ancestral wisdom. Keraton Ismahayana Landak stands as a silent witness to past civilizations and local wisdom, emphasizing the importance of preserving Indonesia's cultural heritage and art